LCC (LIFE CYCLE COST) Analysis On Septic Tank Alternative Types (Case Study Of Housing Pt Baruga Asrinusa Balithai Land Area Phase II, Makassar, Indonesia) - THOENGSAL, JAMES (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
In the planning concept for the housing project, PT Baruga Asri, the Blaithai area, still uses a modular septic tank and is still conventional. Meanwhile, there are alternative choices for the type of Septic tank as a fecal treatment facility which are widely available in the market. The research method uses primary data, with sources of RAB, and Makassar City Work Unit Price Analysis. As well as secondary research methods with sources, from relevant books, and important data about the project such as price lists and wages. It can be concluded that among all Balithai Land housing developments by following the RAB reference for Bukit Baruga Asrinusa housing in the Balithai Land area and AHSP (Work Unit Price Analysis) Makassar city, sanitation work items are one of the work items that can be broken down in terms of the costs involved. also eat up a large budget, even though there are actual work items that cost more. And there was a difference in sanitation work items between the main design and alternative designs of Rp. 148,718.00 and there was 1 alternative design that was raised to replace the existing design currently used, namely by replacing the use of Septic Tank buis concrete Ø80 (4 stacks 2.0 m high) + Cover + Infiltration + 2.5" ventilation pipe with a septic tank with bio capacity of 3-5 0 people. Thus saving the cost of the Bukit Baruga Asrinusa housing development project in the Balithai Land area phase 2. From Rp. 7,025,788.31 to Rp. 6,877,070 ,15.